Data from: Rearing background and exposure environment together explain higher survival of aquaculture fish during a bacterial outbreak ... - Räihä, Ville; Sundberg, Lotta-Riina; Ashrafi, Roghaieh; Hyvärinen, Pekka; Karvonen, Anssi (Dryad, 2019)
1. Parasitic diseases represent one of the greatest challenges for aquaculture worldwide and there is an increasing emphasis on ecological solutions to prevent infections. One proposed solution is enriched rearing, where traditional stimulus-poor rearing tanks are equipped with different types of structures to increase habitat complexity. Such spatial enrichment is known to increase survival of fish during parasite epidemics, but the underlying mechanisms are still unclear. 2. We studied whether enriched rearing affected infection of an important fish pathogen Flavobacterium columnare in young Atlantic salmon (Salmo salar) and sea-migrating brown trout (Salmo trutta). First, we used natural bacterial exposures and multiple fish populations in a common garden experiment to address the role of host genetic background in effects of enriched rearing. Second, fish from standard and enriched rearing were experimentally exposed to controlled bacterial doses in standard and enriched environments in a full factorial ... : Mortality dataThe file contains mortality data of fish species, populations and different rearing treatments in experiment 1, and of fish populations and different rearing/exposure environments in experiment 2.data_Räihä et al.xlsx ...